2022
DOI: 10.55927/fjsr.v1i4.1166
|View full text |Cite
|
Sign up to set email alerts
|

Religious Tourism Development Strategy in Improving Community Economy at Mount Santri, Bojonegara District, Serang Regency, Banten

Abstract: Religious tourism is an activity that is often carried out by most Muslims around the world, including in Indonesia. Pandeglang is part of the province of Banten, where in this area we find many religious tourist attractions, one of which is the religious tourist site of Mount Santri which is located in the Bojonegara District, Serang Regency, Banten, where this place is visited by many pilgrims, both from pilgrims from Serang, as well as from outside Serang. Serang is one of the districts part of Banten provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Service quality is a way of realizing the desires and needs of buyers and delivery provisions to balance consumer expectations (Tjiptono, 2019). Service Quality indicators include: 1) Direct evidence; 2) Reliability; 3) Responsiveness; 4) Guarantee; 5) Empathy; 6) Credibility; 7) Competence; and 8) Communication (Lupiyoadi, 2018) Service Quality has been widely studied by previous researchers including: (Richardo et al, 2020), (Mukhtar et al, 2017), (Masruri et al, 2021), (Doan & Ali, 2021), (Harahap & Ali, 2020), (S. A. H. Havidz et al, 2017, (Sudiantini & Narpati, 2022).…”
Section: Service Qualitymentioning
confidence: 99%
“…Service quality is a way of realizing the desires and needs of buyers and delivery provisions to balance consumer expectations (Tjiptono, 2019). Service Quality indicators include: 1) Direct evidence; 2) Reliability; 3) Responsiveness; 4) Guarantee; 5) Empathy; 6) Credibility; 7) Competence; and 8) Communication (Lupiyoadi, 2018) Service Quality has been widely studied by previous researchers including: (Richardo et al, 2020), (Mukhtar et al, 2017), (Masruri et al, 2021), (Doan & Ali, 2021), (Harahap & Ali, 2020), (S. A. H. Havidz et al, 2017, (Sudiantini & Narpati, 2022).…”
Section: Service Qualitymentioning
confidence: 99%
“…Co-Workers have been studied by many previous researchers, including: (Marasabessy & Santoso, 2014), (Sudiantini & Narpati, 2022), (Husadha et al, 2019), (Narpati, B., & Meutia, 2018), (Havidz & Mahaputra, 2020), (Ilhamalimy & Mahaputra, 2021), (Munawar & Mahaputra, 2022a), (Mahaputra, 2021), (Mahaputra, 2022b).…”
Section: Co Workersmentioning
confidence: 99%
“…Additionally, Sudiantini and Narpati (2022) analyzed Santri mountain religious tourism using a SWOT analysis. They concluded that tourism development could be achieved by increasing the variety of services and products related to the main business and creating products unrelated to the main business, such as selling souvenirs and establishing business cooperation with a profit-sharing system involving multiple parties like the traveling group.…”
Section: Introductionmentioning
confidence: 99%